Correlation between running impacts and VO2max in young football players through GPS technology - Albano, D.; Serra, E.; Vastola, R. (Journal of Human Sport & Exercise, 2019)
This study focuses on the "running" component in football, putting attention to the biomechanical and coordinative aspects rather than to the conditional abilities alone. Poor running technique can be linked to heavy impacts. The objective is to find a correlation between the number of impacts and the VO2max value. Ten young footballers, aged between 13-14 y.o., performed the Gacon test. During the test the number of impacts between 3-5g was recorded with a GPS tracking unit. A correlation was computed between the distance covered and the number of impacts per stage. Another correlation was calculated between the average number of impacts and the number of stages performed. No significant correlation was found between the meters travelled and the number of impacts recorded. On the contrary, a positive correlation (+0.8) was found between the average number of impacts and the total stages performed in the test. Findings suggest the number of impacts does not seem to be indicative of fatigue, while it seems that athletes with a higher V02max (more stages performed) have more impacts than athletes with lower VO2max. It can also be considered that the impacts between 3-5g, not detrimental to the body, are an indicator for good use of the muscular elastic component during the running.